HoNOSCA-D As a Measure of the Severity of Diagnosed Mental Disorders in Children and Adolescents—Psychometric Properties of the German Translation - von Wyl, Agnes; Toggweiler, Stephan; Zollinger, Ruedi (Frontiers in Psychiatry, 2017)
The Health of the Nation Outcome Scales for Children and Adolescents (HoNOSCA), in use worldwide, is a 13-item measure assessing the biopsychosocial severity of mental health problems in children and adolescents. This paper introduces the authorized German-language version of HoNOSCA, the HoNOSCA-D, and examines and discusses its psychometric properties based on a clinical sample of 1,533 children and adolescents aged 4;0 to 17;11 years. For the HoNOSCA-D total score (severity of mental health problems), internal consistency (Cronbach’s alpha) was .63. The discriminative power of the items ranged from .07 to .44; the average inter-item correlation was .11. Due to this stochastic independence, calculation of a total severity index is acceptable. Using factor analysis, the principal axis factoring and varimax rotation resulted in a four-factor structure, which with a Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO) of .684 explained 30.62% of total variance. The convergent correlations with the German-language parent report version of the Strength and Difficulties Questionnaire (SDQ) were as expected and showed a medium effect size. Gender and age differences in the HoNOSCA-D total score were small. Regarding the 13 items gender and age differences were negligible to medium. The highest severity was found for schizophrenia and psychotic disorders, followed by affective disorders and social behavior disorders. Overall, validity of HoNOSCA-D was clearly supported.